STRATEGI PROMOSI EVENT BALI SPIRIT FESTIVAL UBUD - Dilam Arnawa, I Kadek; Sasrawan Mananda, IGPB.; Mahadewi, NPE. (Jurnal IPTA (Industri Perjalanan Wisata), 2024)
Bali Spirit Festival 2023 is the 14th annual Bali Spirit Festival and thousands of people visit this festival every year. In 2023 the Bali Spirit Festival itself has carried out promotions for the domestic market but the level of visits by domestic tourists is still at 15.9%. This research was conducted with the aim of finding out what forms of promotion have been carried out and what alternative promotion strategies are to increase domestic tourist visits to the Bali Spirit Festival 2023. The method used in this research is descriptive qualitative using the SWOT approach and is described using the SWOT matrix. Data collection techniques used in this study were literature studies, interviews, observation and documentation. The informant determination technique used was purposive sampling. The results of this study are that the Bali Spirit Festival conducts advertising in digital and print media, personal selling is carried out by utilizing people who have been involved in the festival, sales promotion is carried out by giving giveaways and price discounts, Bali Spirit Festival public relations always involves the community and has a humanitarian program. and environmental restoration, direct marketing is carried out by marketing its products directly on the website and on the spot. The resulting strategy is the SO Strategy, namely making special promotions utilizing the location and concepts that are owned according to growing trends, providing discounted prices for domestic tourists, maintaining cooperation with the community. ST's strategy is to maintain the concept and uniqueness that is owned, and utilize digital and print promotional media by providing incentives to overcome competition. The WO strategy is to carry out personal sales represented by company personnel to build a good image, the strategy to make special sales that can only be accessed by domestic tourists, and the promotion strategy for the domestic market apart from ex-corporate workers. WT's strategy is to create events that only domestic tourists can participate.